CDH12 as a candidate gene for kidney injury in posterior urethral valve cases: a genome-wide association study among patients with obstructive uropathies - Van der Zanden, Loes F. M.; Rooij, Iris Antonia Leonarda Martina van; Quaedackers, Josine S. L. T.; Nijman, Rien J. M.; Steffens, Martijn; de Wall, Liesbeth L. L.; Bongers, Ernie M. H. F.; Schaefer, Franz; Kirchner, Marietta; Behnisch, Rouven; Bayazit, Aysun K.; Caliskan, Salim; et al. (European urology open science, 2021)
Background - Posterior urethral valves (PUVs) and ureteropelvic junction obstruction (UPJO) are congenital obstructive uropathies that may impair kidney development. - Objective - To identify genetic variants associated with kidney injury in patients with obstructive uropathy. - Design, setting, and participants - We included 487 patients born in 1981 or later who underwent pyeloplasty or valve resection before 18 yr of age in the discovery phase, 102 PUV patients in a first replication phase, and 102 in a second replication phase. - Outcome measurements and statistical analysis - Signs of kidney injury were defined as dialysis, nephrectomy, kidney transplantation, estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2, high blood pressure, antihypertensive medication use, proteinuria, and/or one kidney functioning at <45%. We used χ2 tests to calculate p values and odds ratios for >600 000 single-nucleotide polymorphisms (SNPs) in the discovery sample comparing patients with and without signs of kidney injury within 5 yr after surgery. We performed stratified analyses for PUV and UPJO and Kaplan-Meier and Cox regression analyses in the discovery and two replication samples for the associated SNPs, and RNA and protein expression analyses for the associated gene in fetal tissues. - Results and limitations - Despite the small and nonhomogeneous sample, we observed suggestive associations for six SNPs in three loci, of which rs6874819 in the CDH12 gene was the most clear (p = 7.5 × 10-7). This SNP also seemed to be associated with time to kidney injury in the PUV discovery and replication samples. RNA expression analyses showed clear CDH12 expression in fetal kidneys, which was confirmed by protein immunolocalization. - Conclusions - This study identified CDH12 as a candidate gene for kidney injury in PUV. - Patient summary - We found that variants of the CDH12 gene increase the risk of kidney injury in patients with extra flaps of tissue in the urethra (posterior urethral valves). This is the first report on this gene in this context. Our study provides interesting new information about the pathways involved and important leads for further research for this condition.
Gesehen am 12.07.2021